1997
DOI: 10.1111/j.1651-2227.1997.tb18303.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal care of very‐low‐birthweight infants in special‐care units and neonatal intensive‐care units in Stockholm. Early nasal continuous positive airway pressure versus mechanical ventilation: gains and losses

Abstract: Jdnsson B, Katz-Salamon M, Faxelius G, Broberger U, Lagercrantz H. Neonatal care of very-lowbirthweight infants in special-care units and neonatal intensive-care units in Stockholm. Early nasal continuous positive airway pressure versus mechanical ventilation: gains and losses. Acta Paediatr 1997; Suppl419: 4-10. Stockholm. ISSN 0803-5326.Very-low-birthweight (VLBW) infants are usually intubated at birth and mechanically ventilated at neonatal intensive-care units (NICUs). The objectives of this study were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 23 publications
2
60
1
Order By: Relevance
“…3 A number of observational cohort studies have demonstrated that the use of early CPAP, usually initiated within minutes to hours after delivery, has been associated with a decrease in the use of mechanical ventilation, without any corresponding increases in other morbidities, including death, intraventricular hemorrhage, periventricular leukomalacia, and bronchopulmonary dysplasia. [4][5][6] None of these observations was from prospective controlled trials, and in none was there a contemporaneous control group that did not receive early CPAP.…”
Section: Delivery Room Continuous Positive Airway Pressure/positive Ementioning
confidence: 99%
“…3 A number of observational cohort studies have demonstrated that the use of early CPAP, usually initiated within minutes to hours after delivery, has been associated with a decrease in the use of mechanical ventilation, without any corresponding increases in other morbidities, including death, intraventricular hemorrhage, periventricular leukomalacia, and bronchopulmonary dysplasia. [4][5][6] None of these observations was from prospective controlled trials, and in none was there a contemporaneous control group that did not receive early CPAP.…”
Section: Delivery Room Continuous Positive Airway Pressure/positive Ementioning
confidence: 99%
“…11,12 In Scandinavia, early nCPAP is the first line of treatment for very low-birth-weight infants and many infants can be successfully managed without MV. 13,14 In 1997, Jonsson et al 14 evaluated ventilatory treatment strategies for all infants with a birth weight <1500 g in Stockholm County. Of infants receiving early nCPAP treatment, 34% later required MV and failure of nCPAP was significantly associated with the presence of RDS.…”
Section: Introductionmentioning
confidence: 99%
“…Of infants with the diagnosis of RDS cared for at neonatal units in Stockholm without available MV, 85% had a gestational age of X27 weeks and 91% required transfer for neonatal intensive care. 14 The majority of these infants would likely have benefited from surfactant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these results are not always taken into account in neonatal intensive care units, and MV is often initiated after endotracheal intubation for surfactant administration, without consideration of the fact that many infants who are able to breathe spontaneously could be supported with NCPAP only. [4][5][6][7] The present study was planned to test the hypothesis that preterm infants (Ͻ30 weeks' gestation) with iRDS who were treated with NCPAP and surfactant administration followed by immediate reinstitution of NCPAP could fare better than those who received MV after surfactant administration and who were weaned progressively from MV. In particular, our aim was to determine whether the first strategy could reduce the need for MV during the subsequent clinical course of our patients.…”
mentioning
confidence: 99%